Can we trust the trust words in 10-Ks? - Cho, Myojung (Journal of business ethics, 2024)
We examine the relation between earnings information content and the use of trust words, such as "character," "ethics," and "honest," in the MD&A section of 10-K. We find that earnings announcements of firms using trust words have lower information content than earnings announcements of firms that do not use trust words. We also find that the value relevance of earnings is lower for firms using trust words than those not using trust words. Further, firms using trust words are more likely to receive a comment letter from the SEC, pay higher audit fees, and have lower corporate social responsibility scores. Overall, our results suggest that firms that use trust words in the 10-K are associated with negative outcomes, and trust words are an inverse measure of trust.